Effect of stacking sequence and fiber content on mechanical and morphological properties of woven kenaf/polyester fiber reinforced polylactic acid (PLA) hybrid laminated composites - M. Azlin, M. N.; M. Sapuan, S.; M. Zuhri, M. Y.; S. Zainudin, E. (Elsevier, 2022)
Hybrid laminated composites were fabricated from woven kenaf, woven polyester and polylactic acid (PLA) using the hot compression method. The hybrid composites consist of woven material as reinforcement having the fiber weight-matrix ratio of 40:60. Six samples of hybrid laminated composites were prepared in different stacking sequences using the hand lay-up method. The laminates were prepared and tested based on ASTM International standard method for tensile, flexural and impact properties. S4 samples yield the highest tensile strength, elongation and impact strength among the hybrid composites that were recorded at 103 MPa, 17.88% and 84 kJ/m2, respectively. However, the composition of woven kenaf and woven polyester influenced the result obtained for flexural strength. Higher composition of woven kenaf in hybrid laminated composites exhibited better flexural properties. The tensile fracture surface morphology was evaluated using field emission scanning electron microscopy (FESEM). The data gathered could provide understandings of new hybrid laminated composites for industrial applications such as automotive, structural, and non-structural applications.